Optimizing the efficacy of COVID-19 patient satisfaction surveys in India: A DELPHI- based validation process (One Health & Risk Management, 2024)
Background: The COVID-19 pandemic in India led to a significant increase in healthcare costs and a decrease in patient satisfaction.The aim of this study was to develop and validate a questionnaire to gauge patient satisfaction with healthcare services during the COV-19 period in India.Methods: An e-Delphi method was used to design and validate the questionnaire. The questionnaire consisted of 18 closed -ended questions aimed at assessing patient satisfaction levels among patients affected by the disease. The instrument was validated by a panel of experts, including healthcare professionals, researchers, and public health professionals, using a series of structured rounds.Results: The developed questionnaire was able to capture the multifaceted patient experiences during the period, providing an essential tool for both policymakers and healthcare providers, facilitating a deeper understanding of and response to patient needs. Moreover, the questionnaire was tailored to the cultural and healthcare-specific contexts of the Indian population, considering language, socio-cultural factors, and healthcare practices unique to the region, ensuring the instrument's relevance and effectiveness.Conclusions: This study aims to fill a critical gap in the assessment of patient satisfaction in the context of a healthcare crisis in India, emphasizing the need for use of Delphi Technique for the purpose of validating a questionnaire and obtaining accurate and meaningful data for healthcare improvements and surveys.